A Cross-National Validation of the Academic Expectations Stress Inventory With Chinese and Korean High School Students. (June 2016) - Zhang, Xiaozhou; Tze, Virginia M. C.; Buhr, Erin; Klassen, Robert M.; Daniels, Lia M.
The current study provided evidence for the factor structure of the Academic Expectation Stress Inventory (AESI) in a sample of 213 Mainland Chinese and 184 South Korean high school students. We examined cross-national invariance of the AESI using multiple-group confirmatory factor analysis across two Asian cultural samples. Results suggested a unidimension rather than two-factor structure (self and teachers/parents) in both settings. Results also showed evidence of reliability, convergent validity (significant correlations with depression, emotional exhaustion, and cynicism), and divergent validity (nonsignificant correlations with amotivation and efficacy reduction). ANCOVA results indicated that perceived overall academic expectation stress was significantly higher among Mainland Chinese students than for their South Korean counterparts. Furthermore, there were no differences between males and females for the Korean adolescents while females reported higher expectation scores than males in the Chinese adolescent sample.